Proteomic Characterization of Primary Mouse Hepatocytes in Collagen Monolayer and Sandwich Culture. Issue 1 (14th July 2017) - Orsini, Malina; Sperber, Saskia; Noor, Fozia; Hoffmann, Esther; Weber, Susanne N.; Hall, Rabea A.; Lammert, Frank; Heinzle, Elmar
ABSTRACT: Dedifferentiation of primary hepatocytes in vitro makes their application in long‐term studies difficult. Embedding hepatocytes in a sandwich of extracellular matrix is reported to delay the dedifferentiation process to some extent. In this study, we compared the intracellular proteome of primary mouse hepatocytes (PMH) in conventional monolayer cultures (ML) to collagen sandwich culture (SW) after 1 day and 5 days of cultivation. Quantitative proteome analysis of PMH showed no differences between collagen SW and ML cultures after 1 day. Glycolysis and gluconeogenesis were strongly affected by long‐term cultivation in both ML and SW cultures. Interestingly, culture conditions had no effect on cellular lipid metabolism. After 5 days, PMH in collagen SW and ML cultures exhibit characteristic indications of oxidative stress. However, in the SW culture the defense system against oxidative stress is significantly up‐regulated to deal with this, whereas in the ML culture a down‐regulation of these important enzymes takes place. Regarding the multiple effects of ROS and oxidative stress in cells, we conclude that the down‐regulation of these enzymes seem to play a role in the loss of hepatic function observed in the ML cultivation. In addition, enzymes of the urea cycle were clearly down‐regulated in ML culture. Proteomics confirms lack in oxidative stress defense mechanisms as the major characteristic of hepatocytes in monolayer cultures compared to sandwich cultures. J. Cell. Biochem. 119: 447–454, 2018. © 2017 Wiley Periodicals, Inc. Abstract : Proteomic analyses of primary mouse hepatocytes in collagen monolayer and sandwich culture. Hepatocytes in monolayer culture show more signs of dedifferentiation than in sandwich culture due to their deficiency in oxidative stress defense, actin accumulation and downregulation of the urea cycle.